University extension experienced by academics in education for transformation project - Vieira, Márcia Gilmara Marian (2018)
The extension project aims to promote popular education in health, environment for social, economic and environmental development, stimulating citizen participation as a strategy for change and autonomy. The present report, portrays interdisciplinary experiences lived by academics. The principal objective was to enable different activities like a field trip which primordial purpose was to experience the interaction between education and extension allusive to agroecology and sustainable environmental education, this field trip complements realized activities in the I Extension Seminary of  Education for Transformation. The methodology of the "Circle of Culture" was prioritized for the problematization and reflection of learning, which took place diverse initiatives of promotion of agroecology with the target public giving greater importance disseminate knowledge trough theoretical and practical formation workshops, study groups and seminaries. Therefore, it is noteworthy that this project has become a reality in issues of environment and health.